Al-Quran Arguments in Responding to the Issue of Euthanasia - Wahidin Wahidin; Maghfirah Maghfirah; Johari Johari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The issue of euthanasia, which is death with the help of a doctor, has become a topic of discussion among medical and religious experts. This article aims to analyze Al-Quran Arguments in Responding to the Issues of Euthanasia. This research is a literature review with a descriptive analysis approach, namely explaining the concepts studied comprehensively and then clarifying according to the problem to obtain actual data. The findings obtained in this article are that carrying out active euthanasia is the same as murder because the energetic actions of doctors have taken someone's life on purpose; based on several verses, namely (1) Surah Yūsuf: 87 essentially has given up hope of God's grace; (2) Surah Yūnus: 49, a person has no right to advance or undo someone's death, even though only Allah has the right to this and (3) Surah al-Mā'idah: 32, killing one soul is like killing all souls